What knowledge appears as valid in the subject of Physical Education and Health? A study of the subject on three levels in year 9 in Sweden - Ekberg, Jan-Eric (Physical education and sport pedagogy, 2016)
Background: Many studies have found that Physical Education and Health (PEH) is a popular subject among the majority of pupils. Still, there is an on-going discussion concerning the aim of PEH and what legitimises it as a school subject. It is difficult to identify what knowledge appears as legitimate within PEH, and this creates conflicts within the field. Purpose: The main purpose of this study is to contribute to the on-going debate regarding the knowledge content and the identity problems described in PEH. The conceptual framework used is curriculum theory, inspired by Bernstein's and Lundgren's theoretical work on the social construction of knowledge and the relationship between the production and reproduction of curricular knowledge, further developed by Linde. The specific research questions are the following: (1) What knowledge appears as legitimate in the subject in Sweden on these three levels: In the syllabus, as viewed by teachers, and during the realisation of lessons? (2) What are the similarities and differences between these levels with regard to legitimate subject knowledge? (3) Can we understand the described identity problem in the subject with the help of what knowledge appears legitimate? Research design and data collection: The data used originate from three empirical materials obtained in Sweden from 2003 to 2005: the syllabus valid for compulsory school (i.e. Lpo 94) at the time the interviews and observations took place, material from semi-structured interviews with six PEH teachers who teach year 9 in four different secondary schools, and information from 20 videotaped PEH lessons taught by the interviewed teachers. Findings: The results indicate that one can distinguish two largely dissimilar objects of learning which differ most markedly between the field of formulation and the field of transformation and realisation. The content knowledge of the field of formulation is largely reformulated in the field of transformation, but no major change takes place from the field of transformation to the field of realisation. The 'formulated object of learning' primarily comprises functional physical exercise, conceptual development, and the understanding of health and lifestyles. The 'realised object of learning' consists of formalised sport and physical exercise, with a minor focus on conceptual development. Conclusions: Since two largely different objects of learning emerge in the subject, consensus is low regarding what knowledge is considered legitimate; the knowledge domain on the primary field most likely differs between the two arenas. A main problem for PEH in trying to gain legitimacy is that there are many different actors in the primary field who are related to and have interest in the subject and the knowledge basis of the subject derives from several different academic disciplines and from non-academic ones.